Small-Molecule Binding Aptamers: Selection Strategies, Characterization, and Applications - Ruscito, Annamaria; DeRosa, Maria C. (Frontiers in Chemistry, 2016)
Aptamers are single-stranded, synthetic oligonucleotides that fold into 3-dimensional shapes capable of binding non-covalently with high affinity and specificity to a target molecule. They are generated via an in vitro process known as the Systematic Evolution of Ligands by EXponential enrichment, from which candidates are screened and characterized, and then applied in aptamer-based biosensors for target detection. Aptamers for small molecule targets such as toxins, antibiotics, molecular markers, drugs, and heavy metals will be the focus of this review. Their accurate detection is ultimately needed for the protection and wellbeing of humans and animals. However, issues such as the drastic difference in size of the aptamer and small molecule make it challenging to select, characterize, and apply aptamers for the detection of small molecules. Thus, recent (since 2012) notable advances in small molecule aptamers, which have overcome some of these challenges, are presented here, while defining challenges that still exist are discussed